2007
DOI: 10.1128/jcm.01555-07
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Bloodstream Infections in Adults: How Many Blood Cultures Are Needed?

Abstract: A blood culture is defined as a specimen of blood obtained from a single venipuncture or intravenous access device. There have been numerous changes in blood culture media and systems during the past 30 years (1,3,5,6,8). Newer media reportedly are more sensitive for the detection of microorganisms, and modern, automated, continuous-monitoring blood culture systems (CMBCSs) detect positive results 1 to 1.5 days earlier than previously used conventional blood culture systems (2, 4).Studies reported in the 1970s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
290
3
21

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 434 publications
(341 citation statements)
references
References 7 publications
12
290
3
21
Order By: Relevance
“…In addition, Lee et al . examined 629 patients whose blood culture tests yielded positive results after three or more sets were collected within 24 h; the sensitivity was 73.1% for the first set, 89.7% for the first and second sets, and 98.2% with three sets 19. Based on the above data, we conclude that a minimum of two sets (three sets, if possible) should be collected within 24 h. A further increase in test sensitivity should not be expected if the number of sets collected exceeds three.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Lee et al . examined 629 patients whose blood culture tests yielded positive results after three or more sets were collected within 24 h; the sensitivity was 73.1% for the first set, 89.7% for the first and second sets, and 98.2% with three sets 19. Based on the above data, we conclude that a minimum of two sets (three sets, if possible) should be collected within 24 h. A further increase in test sensitivity should not be expected if the number of sets collected exceeds three.…”
Section: Introductionmentioning
confidence: 99%
“…8,10 Optimally, 3 or 4 blood sets with adequate volume (20-30 mL) obtained within the first 24 hours of suspected bacteremia will have the greatest cumulative yield of pathogens. 11,12 (Four or more sets may be recommended when it is likely that the anticipated pathogens are common contaminants. 1 Table 2 outlines considerations for neonatal, pediatric, and adult blood culture specimens.…”
Section: Single Vs Paired Setsmentioning
confidence: 99%
“…The practice of collecting a single blood culture is contrary to recommendations of collecting 2 to 3 or more blood cultures in cases of suspected bacteremia [12,13]. Although single blood cultures have been shown to detect 91% of BSI episodes [4], they are insufficiently sensitive for detecting some bacteremias and fungemias and they are difficult to interpret [27].…”
Section: Discussionmentioning
confidence: 67%
“…Similarly, Cockerill found that while 2 blood cultures detected only 80% of bloodstream infections, 3 blood cultures detected 96% of episodes [12]. Further research by Weinstein and Reller found that 2 blood cultures obtained during a 24-hour period will detect 89-93% of BSIs in adults, while 3 blood cultures over a 24-hour period will detect all polymicrobial BSIs, and 4 cultures will detect >99.7% of unimicrobial BSIs [3,13].…”
Section: Introductionmentioning
confidence: 99%